Respuesta :

The answer is B, x^2/3

Answer : The correct option is, [tex]x^{\frac{2}{3}}[/tex]

Step-by-step explanation :

The given expression is :

[tex](x^{\frac{4}{3}}\times x^{\frac{2}{3}})^{\frac{1}{3}}[/tex]

First we have to solve the term present in the bracket.

Identity used : [tex]x^a\times x^b=x^{(a+b)}[/tex]

[tex]\Rightarrow (x^{(\frac{4}{3}+\frac{2}{3})})^{\frac{1}{3}}[/tex]

By the adding the powers of 'x', we get:

[tex]\Rightarrow (x^{\frac{6}{3}})^{\frac{1}{3}}[/tex]

[tex]\Rightarrow (x^{2})^{\frac{1}{3}}[/tex]

Now we have to use identity [tex](x^{a})^b=x^{ab}[/tex], we get :

[tex]\Rightarrow (x)^{(2\times \frac{1}{3})}[/tex]

[tex]\Rightarrow (x)^{\frac{2}{3}}[/tex]

Therefore, the correct option is, [tex]x^{\frac{2}{3}}[/tex]

ACCESS MORE